التحول نحو التمويل الإسلامي لإدماج الصناعة المصرفية الإسلامية في البنوك التقليدية الجزائرية "دراسة تطبيقية على البنك الوطني الجزائري بوكالة الشلف": The trend to Islamic finance in the integration of Islamic banking industries into traditional Algerian banks " a case study of the Algerian national Bank agency of chlef " - جزار بديعة أميمة; بشيكر عابد (Journal of North African Economies, 2025)
The aim of this study is to highlight the importance of Islamic banks in facilitating economic and financial transactions, and the need to deal with their Islamic forms and methods of financing to meet the desires of the audience of customers who don’t wish to deal with traditional banks for fear of usury. The public treasury, which is considered a loss for the banking system. Which encouraged Algeria to search for the transformation of conventional banks into Islamic banks. This transformation included the integration of the Islamic banking industry into the Algerian traditional banks. And that using the interview tool with the director of the commercial agency of BNA Bank. The study showed that the experience of involving Algerian government banks in Islamic banking transactions was very successful, because it has helped attracting a large number of dealers who prefer these transactions.